Religious Humanism In Islamic Education: A Comparative Study Of The Thoughts Of Abdurrahman Wahid And Nurcholish Madjid And Its Implications For Multicultural Education In Indonesia - Muhammad Masyhuri; Jalaluddin Suyuthi Winulyo; Benny Prasetya (PT. Education Research Center, 2026)
This study aims to analyse the conceptual construction of religious humanism in Islamic education as an integrative paradigm between divine and human values. It is motivated by the epistemological dichotomy between theocentric and anthropocentric approaches in educational praxis, which often results either in a normative-dogmatic orientation lacking social sensitivity or, conversely, in a humanistic approach detached from transcendental foundations. Employing a qualitative design based on library research, this study utilises a descriptive-critical analysis of relevant primary and secondary sources. The findings demonstrate that religious humanism in Islamic education affirms the integration of the values of tawhid (divine unity), justice, compassion, and respect for human dignity as beings endowed with an innate disposition (fitrah). This paradigm positions learners as active subjects who possess spiritual, intellectual, and social potential that must be developed holistically. Islamic education grounded in religious humanism is oriented not merely towards the transmission of knowledge, but also towards character transformation and the cultivation of ethical and spiritual consciousness. Thus, religious humanism functions as both a normative and practical framework that remains relevant in addressing the challenges of modernity while preserving the authenticity of Islamic values within the educational system.